Feminist measures in survey research - Harnois, Catherine E. (SAGE, 2013)
This book offers a new approach for doing quantitative feminist research, demonstrating how a feminist perspective can inform virtually every aspect of the research process, from survey design, to statistical modelling, to the theoretical frameworks used to interpret results. Catherine E. Harnois makes feminist theory, particularly multiracial feminist theory, accessible and relevant to survey researchers. She assists students and researchers in incorporating these theories into survey design and analysis and shows how this can offer substantive insights into the social world that have been underutilized to date by survey researchers.